Linking Industrialization and Education in Sub-Saharan African Countries - Valery, Moutie Giscard; Che, Gladys Njang; Nkemgha, Guivis Zeufack (Asian Journal of Empirical Research, 2022)
Several works have studied the consequences of industrialization on macroeconomic variables. However, the relationship between industrialization and education has not yet been studied, especially in sub-Saharan Africa (SSA). The objective of this study is to fill this limitation of the literature by analyzing the direct effect of industrialization on education in 23 SSA countries during the period 2000-2018. Moreover, we analyzed the indirect effect between the two variables through the transmission channels. To achieve our objective, we mobilized the Driscoll and Kraay methods and System GMM. The results reveal that there is a negative and significant relationship between industrialization and education. Moreover, urbanization and per capita income are transmission channels that contribute to mitigating this negative effect. Finally, our results show that the positive impact of the processing sector on education in SSA is conditioned by the achievement of a certain per capita income threshold and a certain urbanization threshold.